2001
DOI: 10.3171/foc.2001.11.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in intracranial pressure in a modified experimental model of closed head injury

Abstract: Object The authors describe an experimental model of closed head injury in rodents that was modified from one developed by Marmarou and colleagues. This modification allows dual control of the dynamic process of impact compared with impulse loading that occurs at the moment of primary brain injury. The principal element in this weight-drop model is an adjustable table that supports the rat at the moment of impact from weights positioned at different heights (accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 21 publications
2
29
0
1
Order By: Relevance
“…7,28 In previous rat experiments, others have shown that intra-and extracellular edema formation peaks from 12 hours to 2 days following contusion, 3,15 which corresponds to a peak in the intracranial pressure. 9 Many different descriptors are used for designating the physical properties of materials, and lay usage does not always equal the scientific definitions. Hardness is a measure of the resistance of solid matter to permanent shape change when a force is applied; it is dependent on other parameters, including stiffness (an elastic body's resistance to a rapidly deforming force), elasticity (return to original shape after withdrawal of a deforming force), strength (ability to withstand an applied force without failure), plasticity (permanent deformation after a force ) performed on rat intracranial contents with the dura intact.…”
Section: Discussionmentioning
confidence: 99%
“…7,28 In previous rat experiments, others have shown that intra-and extracellular edema formation peaks from 12 hours to 2 days following contusion, 3,15 which corresponds to a peak in the intracranial pressure. 9 Many different descriptors are used for designating the physical properties of materials, and lay usage does not always equal the scientific definitions. Hardness is a measure of the resistance of solid matter to permanent shape change when a force is applied; it is dependent on other parameters, including stiffness (an elastic body's resistance to a rapidly deforming force), elasticity (return to original shape after withdrawal of a deforming force), strength (ability to withstand an applied force without failure), plasticity (permanent deformation after a force ) performed on rat intracranial contents with the dura intact.…”
Section: Discussionmentioning
confidence: 99%
“…The later result can exist because low concentration of phytoestrogens might not be adequate to fully activate the neuroprotective pathways [19] for prohibiting ICP elevation on days post-TBI. The causes of the ICP increase in TBI could be hypoxia [45], the reduction of cerebral blood flow [46], cerebral edema [47], ischemic injury, hyper-perfusion in the early stages after TBI [48], changes in the expression of aquaporin-4 [49] and vaso-paralysis, and impaired auto-regulation [50]. It seems that our study is the first to evaluate the effect of soy on ICP.…”
Section: Discussionmentioning
confidence: 99%
“…Many experimental models were performed in the last decades so as to reproduce head trauma in laboratory [1][2][3] .A group of these studies uses the weight drop right trauma model mechanism or produces encephalic lesions through using pneumatic pistons regulated by compressed air 10 . The head trauma experimental models intend to reproduce the complex physiopathology of traumatic brain injury in laboratory in order to allow the development of new therapeutic approaches 1,2 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the model uses simple physical principles to produce a closed head injury and was prepared by using descriptions of other similar instruments reported in literature 3,4,6 that were already used in head trauma experimental surgery researches at the experimental surgery laboratory from Piaui State University (UESPI). Silva et al 7 , as well as the study developed by Dixon et al 8 with controlled cortical impact in rats, investigated systematically the effects of different levels of energy in closed head trauma in rats considering neurological, cardiovascular and histopathologycal variants, and this article have detailed the last parameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation